Diagnosing adults with dyslexia: Psychologists' experiences and practices. (15th July 2021) - Sadusky, Andrea; Reupert, Andrea E.; Freeman, Nerelie C.; Berger, Emily P.
Abstract : Previous research has investigated how psychologists identify dyslexia in school‐aged children. However, it is presently unclear how psychologists diagnose dyslexia in adults. This study aimed to explore psychologists' understandings and experiences in how they assess adults for dyslexia. Nine psychologists in Australia were recruited from professional associations and interviewed using a semi‐structured schedule. After member checks, transcripts were analysed using reflexive thematic analysis. The results suggested that participants' assessment practices with adults were similar to those used with children. However, participants were not confident in assessing adults due to a lack of an empirical base and training, and appropriately normed tools. Moreover, participants relied on their clinical judgment to help overcome barriers unique to the assessment of adults including obtaining an accurate developmental history and determining the relevancy of academic intervention for a formal diagnosis. Participants recommended (better) training and accessible research about how to efficaciously diagnose adults with dyslexia. The robustness of current diagnostic tools for equitably identifying adults with dyslexia was questioned by some participants. There is a need for national guidelines in Australia to support psychologists in identifying adults with dyslexia. International research and guidelines have an important role to play in informing this process.